Ag/TiO2 nanocomposite for visible light-driven photocatalysis. (November 2018) - Sanzone, G.; Zimbone, M.; Cacciato, G.; Ruffino, F.; Carles, R.; Privitera, V.; Grimaldi, M.G.
Abstract: In the last few years TiO2 -based materials have been extensively studied due to the effectiveness in water decontamination. The main issue to overcome for a real sun driven application of this emerging technology is to use the visible part of the solar spectrum. It is known that the presence of metal nanoparticles improves the efficiency of TiO2 due to several factors, including localized surface plasmon resonance and scavenging of electrons. In this work, we demonstrate that the optical properties of the Ag nanoparticles and of the supporting film (TiO2 matrix) are critical aspects for the activation of the photocatalytic response of the nanocomposite material. We propose the use of an Ag-TiO2 nano-engineered film for visible-driven photocatalysis. We successfully demonstrated that a proper control of the TiO2 substrate film thickness is able to enhance the photocatalytic response of the film thanks to a field enhancement effect. In particular, we matched the optical reflectance, peculiar of a thin film, with the localized surface plasmon resonance and the wavelength used for the photocatalytic experiment and observed an enhancement of the activity. Graphical abstract: Highlights: Discoloration of Methylene blue, using Ag nanoparticles embedded in a TiO2 thin film, with visible light is achieved. The maximum discoloration efficiency is obtained for titanium dioxide nanocomposite thin film in antireflective condition. Nanocomposite photoactivity in the visible range is due to localized surface plasmon resonances.